2023
DOI: 10.1021/acsaenm.3c00415
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Adsorption of Th(IV) and U(VI) Ions from Aqueous Solutions by a Tannic-Acid-Modified Nanomagnetite Adsorbent

Manish Sharma,
Pranali Dhiware,
Priya Sharma
et al.

Abstract: Nuclear wastewater remediation provides an intriguing opportunity to successfully remove and recover radioactive elements, especially Th(IV) and U(VI) ions, since they play a crucial role as nuclear fuel and pose a significant threat to the sustainability of the environment. In the present investigation, magnetic nanoparticles were modified by a polyphenolic compound, tannic acid (TA), to develop a tannic acid@magnetite (TA@Fe3O4) nanocomposite for effective adsorption of Th(IV) and U(VI) ions from wastewater.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 80 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…In this aspect, 30 mg of uranium and thorium ion loaded adsorbent was immersed in 50 mL of 0.1 M HCl solution and agitated on a shaker for 3 h. After desorption of uranium and thorium ions, beads were washed with distilled water and collected through the external magnet, dried in a hot air oven at 40 °C for 8 h, and then reused for further adsorption studies. In the acidic medium, hydrogen bonds got weakened between the uranium and thorium ions and MNPs-SA@Cu MOF composite beads and desorption takes place. , It can be seen from Figure a, beads showed the ten adsorption–desorption cycles with a slight decrease in the removal efficiencies of U­(VI) (99.99 to 92%) and Th­(IV) (97.78 to 89.25%) without the demolition of the beads. Recovery of uranium and thorium ions have also been checked after desorption.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this aspect, 30 mg of uranium and thorium ion loaded adsorbent was immersed in 50 mL of 0.1 M HCl solution and agitated on a shaker for 3 h. After desorption of uranium and thorium ions, beads were washed with distilled water and collected through the external magnet, dried in a hot air oven at 40 °C for 8 h, and then reused for further adsorption studies. In the acidic medium, hydrogen bonds got weakened between the uranium and thorium ions and MNPs-SA@Cu MOF composite beads and desorption takes place. , It can be seen from Figure a, beads showed the ten adsorption–desorption cycles with a slight decrease in the removal efficiencies of U­(VI) (99.99 to 92%) and Th­(IV) (97.78 to 89.25%) without the demolition of the beads. Recovery of uranium and thorium ions have also been checked after desorption.…”
Section: Resultsmentioning
confidence: 97%
“…In the acidic medium, hydrogen bonds got weakened between the uranium and thorium ions and MNPs-SA@Cu MOF composite beads and desorption takes place. 57,58 It can be seen from Figure 12a ), chloride (Cl − ), calcium (Ca 2+ ), magnesium (Mg 2+ ), and fluoride (F − ) (50 ppm) were used, and adsorption study was done under optimized conditions (pH = 6, 10 mL of 50 mg/L of U(VI) and Th(IV) solution, 6 mg dose). As shown in Figure 12b, no significant impact was seen on the adsorption of U(VI) and Th(IV) ions in the presence of various ionic salts.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For this, three kinetic linear model equationspseudo-first-order (PFO), pseudo-second-order (PFO), and intraparticle diffusion­(IPD)were used for the adsorption studies (Text S2). Figure S10a,b shows the linear fitting of kinetics models as a function of time, and Table shows all the kinetic parameters. From the table, it is evident that the adsorption kinetics of the removal of BZ were better described by the PSO model, which had the higher regression coefficient value (0.9912) compared to PFO model.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The physical properties, including surface area, pore diameter, and pore volume, of Zn–Cu-BDC and Zn–Cu-BDC@CA CBs were systematically investigated using BET analysis, as illustrated in Figures S2 and d. Nitrogen adsorption–desorption isotherms revealed that both Zn–Cu-BDC and Zn–Cu-BDC@CA composites exhibit type-III isotherms characterized by the presence of a H3-type hysteresis loop. , Detailed results obtained from the BET analysis for Zn–Cu-BDC and Zn–Cu-BDC@CA CBs are tabulated in Table S1. The Zn–Cu-BDC@CA CBs have lower value of BET parameters, which may be possible due to the filling of pores with sodium alginate.…”
Section: Resultsmentioning
confidence: 99%